G463(P) First case of constitutional mismatch repair deficiency syndrome associated with bronchiectasis. (12th March 2018) - Swinburne, C; Barclay, A; Beattie, PE; Davidson, R; Murphy, D; O'Kane, R; Zuberi, S; Devenny, A
Abstract : Introduction: Constitutional mismatch repair deficiency (CMMRD) syndrome is a rare autosomal recessive disorder that results from homozygous germline mutations in one of the mismatch repair genes MLH1, MSH2, MSH6 and PMS. CMMRD syndrome results in a predisposition to childhood malignancy, with an increased risk of developing central nervous system (CNS), haematological and gastro-intestinal (GI) tract cancers. Colorectal polyps and cutaneous manifestations resembling neurofibromatosis type 1 are common. We present the case of a patient with CMMRD syndrome and bronchiectasis, an association not previously documented in the literature. Case report: A 13-year-old boy of Pakistani origin born to consanguineous parents was referred to the paediatric outpatient clinic with anaemia. Both parents had a diagnosis of Lynch syndrome and elder brother a diagnosis of CMMRD syndrome with a previous history of CNS primary neuro-ectodermal tumour and basal cell carcinoma. Consultation revealed a history of chronic productive cough and recurrent lower respiratory tract infections with evidence of finger clubbing on examination. Cutaneous manifestations included a large scalp congenital melanocytic naevus, multiple CALMs, hypopigmented lesions and axillary and inguinal freckling. Persistent left lower lobe changes were noted on chest X-ray. Bronchoscopy demonstrated normal airway anatomy with increased secretions noted from left lower lobe bronchus. CT chest confirmed a diagnosis of bronchiectasis. Sweat test and ciliary biopsy were normal. Immunoglobulin A was low at <0.7 g/L while lymphocyte subset analysis was unremarkable. Baseline pulmonary function testing demonstrated a moderate restrictive defect with no evidence of obstruction. Genetic screening was performed in light of family history which identified a familial homozygous MSH6 sequence variant, c.3175del p.(Val1059fs), consistent with a diagnosis of CMMRD syndrome. Bowel screening was undertaken and colonoscopy identified a large colorectal villous adenoma with focal high-grade dysplasia. The patient subsequently developed focal seizures and was diagnosed with a right fronto-parietal brain tumour with three metastatic lesions. Biopsy, although not conclusive, was felt to be representative of a high-grade glial or embryonal tumour. Conclusion: CMMRD syndrome is associated with a complex array of clinical manifestations and a wide tumour spectrum. Bronchiectasis has not been previously documented in the literature and should be considered where a history of chronic respiratory symptoms exists.